Literary “abroad”: Ahmad Fuadi in the Indonesian’s Literary Arena: Sociology of Literature’s Study - Nurhayati, Hawin (Udayana Journal of Social Sciences and Humanities; Vol 3 No 2 (2019): UJoSSH, September 2019, 2019)
Behind the success of the authors, letters, and/or novelists, there are some interesting wrestlings from their position in the Indonesian literary arena. For some of them, success is not only creating work, then read and bought. A recognition is more important, to have a more important position than being ‘author' only. This case urges the researcher to conduct this research, about the position of a popular novel author, Ahmad Fuadi. Bourdeau (in Karnanta, 2013) by his concept, heterodoxa, discussed the explicit thought shared about whether legal or not of the perception and appreciation currently in effect. The investigation towards Ahmad Fuadi's position in the Indonesian's literary arena by using the sociology literature approach resulted that he never asked for his literary position, although he has international and well-appreciated works. For him, the most important is working, worshipping, continuously ‘going abroad' for studying and ‘broadening' knowledge toward others by his work.